Seasonal incidence of insect pests and their natural enemies in mustard ecosystems: A comprehensive review (Journal of Oilseed Brassica, 2026)
Mustard (Brassica spp.) is a major oilseed crop in India and is prone to attack by a wide range of insect pests throughout its growth stages, leading to substantial yield losses. Among these, the mustard aphid Lipaphis erysimi (Kalt.), mustard sawfly Athalia lugensproxima, flea beetle Phyllotreta cruciferae, and painted bug (Bagrada cruciferarum and B. hilaris) are of major economic importance. This review synthesizes decades of research on the seasonal incidence, population dynamics, and influencing meteorological parameters of these pests, along with the occurrence of their natural enemies. Studies consistently reveal that L. erysimi appears from November to April, with peak activity during January-February under temperature ranges of 17-24°C and relative humidity between 60-85%. Rainfall exerts variable effects, with light showers favouring population build-up and heavy rains causing dislodgement. Mustard sawfly incidence generally begins in October-December, with optimal development at temperatures between 19-30°C, while flea beetle populations peak in February. Painted bugs show seedling-stage damage and activity peaks either in winter or during crop maturity depending on the species. Natural enemies, particularly Diaeretiella rapae, Coccinella septempunctata, Cheilomenes sexmaculata, syrphid flies, and lacewings, play a vital role in pest suppression, with parasitism levels often exceeding 80-90% during late crop stages. Temperature, humidity, sunshine hours, wind velocity, and crop phenology significantly influences the timing and intensity of both pest and predator populations. Understanding these seasonal patterns are critical for developing timely, ecologically sound pest management strategies in mustard cultivation.